Karakteristik Brownies dengan Perbedaan Lama Fermentasi Tepung Mocaf sebagai Bahan Subtitusi: Characteristics of Brownies with Differences of Fermentation Time of Mocaf Flour as Substitute Ingredients - Febrina, Asti; Maryam, Andi; Khadijah, Khadijah (JURNAL AGROINDUSTRI HALAL, 2022)
The purpose of this study was to examine the effect of the content of mocaf flour with different fermentation times on the quality of brownies. This study used a completely randomized design method. The samples used were mocaf flour brownies which were then handed over to the panelists, each panelist getting 4 samples of mocaf flour brownies. Sample codes to be given are A (24), B (48), C (72), and D (96). Analysis of mocaf flour brownies, namely water content and protein content. The results of the organoleptic test showed that sample D was the most preferred brownie with a percentage of 6.40 (Aroma), 6.90 (Taste), 6.87 (Texture). The results of the water content test are that the water content in sample A is 10.87%, sample B is 10.67%, sample C is 10.32% and sample D is 9.63%. The difference in fermentation time affects the protein content of mocaf flour. It can be seen from the test results obtained that sample A is 0.19%, sample B is 0.35%, sample C is 0.19% and sample D is 0.12%. It can be seen from the results of the brownie protein content test that the sample A obtained was 2.31%, sample B was 2.78%, sample C was 3.63% and sample D was 4.32%. It can be concluded that there is an effect of mocaf fermentation time on the moisture content and protein content of brownies.